The Role of Indicators, Targets and Monitoring in Decision-Support for Transport - Marsden, Greg; Snell, Carolyn (European Journal of Transport and Infrastructure Research, 2009)
Indicators can be seen as crucial to the transport planning processes as they can be used for decision-support in all aspects of policy development and assessment from option generation, through policy testing and appraisal to monitoring and feedback. Indicators are however, also seen by many practitioners as artificially focussing transport policy on what can be counted and on which indicators can most easily be improved. This paper presents the findings of a four year study into the use of indicators in the UK. In response to requests from local government practitioners, the research developed advice on how to develop a coherent indicator framework. The framework was tested through application in four case studies. The implications of the application of the framework are described in the paper and the degree to which the main criticisms of indicators can be overcome assessed. Many of the criticisms levelled at indicators such as their role in the distortion of decision-making processes arise not because indicators inevitably lead to significant conflicts but because of poor internal planning processes or unnecessary external constraints. The evidence presented in this paper suggests that, developed properly, an indicator framework is an essential part of an effective transport planning process for internal management and decision support and for external communication. Advice is provided on the conditions necessary for the development of an effective framework.